Genetic engineering for improvement of Musa production in Africa - Tripathi, L. (Academic Journals, 2003)
Bananas and plantains (Musa sp.) are the most important staple food and source of carbohydrates in many countries of Africa. The production is often constrained by many pests and diseases. In order to augment conventional breeding and to avoid constraints imposed by some pests and pathogens, transgenic approaches are being considered. The development of transgenic Musa plants has been achieved recently using the microprojectile bombardment procedure or Agrobacterium-mediated transformation. The transgenic approach shows potential for the genetic improvement of the crop using a wide set of transgenes currently available which may confer resistance to nematode pests, fungal, bacterial and viral diseases. This article discusses the applications of genetic engineering for the enhancement of Musa production.